Creating percutaneous radiocephalic arteriovenous fistulas at the wrist. Issue 2 (March 2021) - Mallios, Alexandros; Nelson, Peter R; Franco, Gilbert; Jennings, William C
Background: The first arteriovenous fistulas were created at the wrist more than 60 years ago. Basic surgical construction techniques remain unchanged with mobilization and repositioning of the vessels followed by a sutured anastomosis. We used the Ellipsys device to construct percutaneous radiocephalic–arteriovenous fistulas at the wrist and report the results. Methods: Data were reviewed retrospectively for all patients who had a percutaneous radiocephalic–arteriovenous fistula created during a 6-month period. Each individual underwent ultrasound vessel mapping in addition to physical examination. When a radiocephalic–arteriovenous fistula was feasible and a communicating vein ⩾ 2 mm in diameter was noted in the distal forearm along with a radial artery ⩾ 2 mm, a percutaneous radiocephalic–arteriovenous fistula was considered and reviewed with the patient. Results: Four individuals met the criteria to consider a percutaneous radiocephalic–arteriovenous fistula and all elected to have the procedure performed. Ages were 54–85 years. Three were diabetic and one was female. All percutaneous radiocephalic–arteriovenous fistulas were technically successful. Two individuals had not yet started dialysis therapy. Successful and repetitive cannulation for the two individuals with catheters was initiated at 4 and 8 weeks post procedure. The two pre-dialysis patients had physiologic arteriovenous fistula maturation (6 mm vein diameter and >500 mL/min flow) at 4 and 12 weeks. There were no procedural or late complications and none required intervention. Follow-up was 8–23 months (mean 16 months). Conclusion: The success of these percutaneous radiocephalic–arteriovenous fistulas suggests that use of the Ellipsys device will be applicable at the wrist in selected patients where appropriate vessel sizes and configurations are found.